(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Phytopathogenic viruses are a significant threat to global agriculture, causing substantial losses in crop yields and quality. These viruses not only affect plant growth but also induce a range of physiological and biochemical changes that alter plant health. This article reviews the effects of phytopathogenic viruses on plant physiological processes such as growth, photosynthesis, respiration, and nutrient uptake, as well as biochemical changes, including alterations in metabolic pathways and enzyme activities. The disruption of these processes can lead to reduced plant productivity, diminished quality, and in severe cases, plant death. Understanding these virus-induced changes is critical for developing effective strategies to manage viral infections in crops. Additionally, the article explores how plants respond to viral infection through biochemical defense mechanisms, such as the production of reactive oxygen species (ROS) and the activation of systemic resistance. This review aims to provide a comprehensive understanding of the complex interaction between phytopathogenic viruses and plant systems, highlighting the need for continued research to mitigate the impacts of these viruses on agricultural productivity.